Mental health literacy and its associated factors among parents and teachers of secondary school students in peninsular Malaysia - Ann, Picholas Phoa Kian (2023)
The increase in mental health and suicide issues among adolescents calls for the need to improve the parents, caregivers, and teachers’ mental health literacy (MHL) and suicide literacy (SL) to ensure adequate knowledge to provide initial mental health support. The current study aimed to evaluate the levels of mental health and suicide literacies and identify their associated demographic factors. The crosssectional study recruited 867 participants (parents and teachers) across 24 government secondary schools in West Malaysia sampled via a multistage stratified cluster sampling method. The current study used the 12-item Malay Mental Health Knowledge Schedule (MAKS-M) and the 26-item Malay Literacy of Suicide Scale (M-LOSS) to assess mental health and suicide literacies. The mean score of overall MHL for the current study sample was 43.82 (SD = 4.07). Study results showed significant mean differences between sexes, religions, education levels, income brackets, had known someone with a mental disorder, had assisted someone with a mental illness, and attended formal training for psychological first aid. Participants who scored higher on their MHL level tend to be female, had known someone with a mental disorder, had assisted someone with a mental disorder, and attended formal psychological first aid training. Upon regression, age, income brackets, knowing someone with mental disorder, and attended formal psychological first aid training were the significant predictors of MHL. As for the SL, the current population scored 54.0% (M = 14.05, SD = 2.61), with the highest rate of correct responses on the treatment and prevention subscale, followed by the risk factors subscale, signs and symptoms subscale, and the lowest in the causes and nature subscale. The mean score difference was found to be significant between school types. There is a significant negative correlation between age and mean SL score, and age was the unique predictor of SL level. Finally, no significant association was found between MHL and SL. The study findings can be used as a foundation for MHL and SL research among the local Malaysian community to guide the development of effective evidence-based intervention programmes for mental health and suicide.